Injury-experienced satellite cells retain long-term enhanced regenerative capacity - Jacopo Morroni; Anna Benedetti; Lorenza Esposito; Marco De Bardi; Giovanna Borsellino; Carles Sanchez Riera; Lorenzo Giordani; Marina Bouche; Biliana Lozanoska-Ochser (Stem Cell Research & Therapy, 2023)
Abstract Background Inflammatory memory or trained immunity is a recently described process in immune and non-immune tissue resident cells, whereby previous exposure to inflammation mediators leads to a faster and stronger responses upon secondary challenge. Whether previous muscle injury is associated with altered responses to subsequent injury by satellite cells (SCs), the muscle stem cells, is not known. Methods We used a mouse model of repeated muscle injury, in which intramuscular cardiotoxin (CTX) injections were administered 50 days apart in order to allow for full recovery of the injured muscle before the second injury. The effect of prior injury on the phenotype, proliferation and regenerative potential of satellite cells following a second injury was examined in vitro and in vivo by immunohistochemistry, RT-qPCR and histological analysis. Results We show that SCs isolated from muscle at 50 days post-injury (injury-experienced SCs (ieSCs)) enter the cell cycle faster and form bigger myotubes when cultured in vitro, compared to control SCs isolated from uninjured contralateral muscle. Injury-experienced SCs were characterized by the activation of the mTORC 1 signaling pathway, suggesting they are poised to activate sooner following a second injury. Consequently, upon second injury, SCs accumulate in greater numbers in muscle at 3 and 10 days after injury. These changes in SC phenotype and behavior were associated with accelerated muscle regeneration, as evidenced by an earlier appearance of bigger fibers and increased number of myonuclei per fiber at day 10 after the second injury. Conclusions Overall, we show that skeletal muscle injury has a lasting effect on SC function priming them to respond faster to a subsequent injury. The ieSCs have long-term enhanced regenerative properties that contribute to accelerated regeneration following a secondary challenge.